HIV AWARENESS AMONG GENERAL POPULATION IN DURG DISTRICT - Dr. Atul G. Agrawal (International Journal of Medical Science And Diagnosis Research, 2018)
Objectives To assess the awareness and attitude of the general public toward people living with HIV/AIDS in Durg District Chhattisgarh. Design: Community-based cross-sectional study. MATERIALS AND METHODS: This is a community-based cross-sectional study done among 277 people in UHTC of Chandulal Chandrakar Memorial Medical College. The selection of subjects under study was done using convenient sampling technique. Subjects were individually approached and an informed consent was obtained. Consent of respondents less than 18 years of age was taken from their parents. The respondents were assured of their confidentiality. Data collection was done for 3 months, from October to December 2018 using a predesigned and pretested questionnaire. The questionnaire consist of demographic characteristics (age, sex, marital status, education, occupation), questions about organism causing the disease, modes of transmission, modes of prevention and attitude towards people living with HIV/AIDS. Data was entered and analyzed in Microsoft Excel 2013 software. Descriptive statistics were obtained and results were expressed as proportions. OBSERVATIONS AND RESULTS: The study subjects ranged from 15 to 80 years of age. Overall 306 people were surveyed out of which 277(90.5%) have heard about HIV/AIDS whereas 29(9.5%) have not heard about the disease. Only 277 respondents who have heard about HIV/AIDS were analyzed further under three broad categories of knowledge regarding disease, preventive measures for the disease and attitude towards the people living with HIV/AIDS. Among 277 respondents who heard about HIV/AIDS, 143(51.6%) were male and 134(48.4%) were female. The mean age of the respondents was 34.2 years with standard deviation of 12.4 years. Among all the participants, only 33.6% are aware that HIV is caused by virus. 52% has no idea about causative organism. 9.7% think HIV is caused by bacteria. 3.2% say parasite causes the disease whereas 1.4% think that disease is caused by fungus. 22.7% among all the respondents know there is difference between HIV and AIDS. 24.2% think there is no difference between HIV and AIDS. 53.1% don’t know if there is any difference between HIV and AIDS. CONCLUSION: In present study majority of the respondents has shown positive attitude and said they will behave friendly with person(s) suffering from HIV/AIDS. A similar study reported that 50% responded with isolation of diseased/infected people from society